PROFIL BERPIKIR KRITIS SISWA KELAS VII MTs NEGERI JEMBER 1 FILIAL DALAM MENYELESAIKAN SOALOPERASI HITUNG BILANGAN PECAHAN BERDASARKAN GENDER - Krisagotama, Fisdianti; Susanto, Susanto; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2015)
Abstract.This research aimsto describethe students' critical thingking profile according to gender in solving mathematics problem of arithmetic operation sub subject of fraction at seventh grade MTs Negeri Jember 1 Filial. The standart of critical thingking in this research consist of clarity, precision,accuracy, relevance, consistency, logical correctness, completeness, andfairness. The instruments in this research are mathematicstest and interview guidelines. This research subject is all of the seventh grade students at MTs Negeri Jember 1 Filial.Six students of them as the representative good communication consist of 3 female students and 3 male students. Male students not appropriate with all of critical thingking standart. They are understand of the question in the mathematics test but actually they cannot resolve those mathematics test. Famalestudents mostly appropriate with all of clarity and fairness critical thingking standart. They are understand of the problem in the mathematics test but accualy they cannot resolve those mathematics test correctly. Key Words: Critical Thingking, Gender, and Arithmetic Operation Sub Subject of Fraction